eAccess to Justice - Bailey, Jane; Steeves, Valerie (Law, Technology and Media, 2016)
How can we leverage digitization to improve access to justice, without compromising the fundamental principles of our legal system? eAccess to Justice describes the many challenges that come with the integration of information and communication technologies into our courtrooms, and explores lessons learned from digitization projects from around the world. Edited by Jane Bailey and Valerie Steeves. Contributions by Trevor Scott Milford; Akane Kanai; Assumpta Ndengeyingoma; Jacquelyn Burkell; Madelaine Saginur; Priscilla M. Regan; Diana L. Sweet; Jessica Ringrose; Laura Harvey; Jordan Fairbairn; Andrea Slane; Shaheen Shariff; Ashley DeMartini; Gillian Angrove; Matthew Johnson; Sarah Heath; Betsy Rosenblatt; Rebecca Tushnet; and Leslie Regan Shade. Keywords: Privacy, identity, equality, online environment, women, cyberfeminism, policy